Vocal activity as a welfare indicator in killer whales in managed care - Almunia, Javier; Lüke, Jonas Philipp; Rosa, Fernando (Frontiers in Marine Science, 2025)
IntroductionMonitoring acoustic activity is a promising approach for assessing animal welfare in cetaceans. In particular, variations in vocal production may reflect changes in arousal and emotional state, which are critical components of welfare.MethodsWe implemented a long-term passive acoustic monitoring system to continuously record the vocal activity of a group of five killer whales (Orcinus orca) under human care at Orca Ocean, Loro Parque. Using a custom detection algorithm and classification criteria, we focused on quantifying the rates of discrete call production throughout the day and across different seasons.ResultsThe results revealed strong diel patterns in vocal activity, with increased rates during the day, particularly around feeding and training sessions, and minimal vocal activity overnight. Additionally, we observed seasonal variability, with higher overall call rates during the summer and autumn months. These fluctuations suggest that vocal activity may be influenced by both scheduled events and environmental conditions.DiscussionOur findings support the use of passive acoustic monitoring as a tool to identify behavioural rhythms and potential indicators of arousal in orcas. This approach may contribute to welfare assessment protocols by providing non-invasive, continuous data on vocal behaviour. Moreover, the system demonstrated robust performance over extended periods, confirming its suitability for long-term implementation in both managed and wild populations.